2021
DOI: 10.3390/cimb43030114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin D Supplementation on Inflammatory Markers’ Levels in Obese Patients

Abstract: In view of research suggesting a possible beneficial impact of vitamin D on systemic inflammatory response, the authors decided to investigate an influence of vitamin D supplementation on serum levels of certain inflammatory markers in obese patients. The current study included such biomarkers as interleukin-6 (IL-6), pituitary adenylate cyclase-activating peptide (PACAP), advanced oxidation protein products (AOPP), C-X3-C Motif Chemokine Ligand 1 (CX3CL1), monocyte chemoattractant protein-1 (MCP-1), and nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Vitamin D supplementation increases the levels of anti-inflammatory cytokines (IFN-γ and IL-10) in subjects with normal weight and vitamin D insufficiency [ 134 ]. While some studies have suggested that increased serum 1,25(OH) 2 D 3 concentrations are associated with decreased inflammatory marker expression in individuals with normal weight [ 135 ], other research has found no significant effects of vitamin D on inflammatory biomarkers in patients with obesity [ 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ]. Furthermore, studies on the effect of vitamin D supplementation on CRP serum levels in patients with obesity have yielded conflicting results [ 137 , 138 , 139 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D supplementation increases the levels of anti-inflammatory cytokines (IFN-γ and IL-10) in subjects with normal weight and vitamin D insufficiency [ 134 ]. While some studies have suggested that increased serum 1,25(OH) 2 D 3 concentrations are associated with decreased inflammatory marker expression in individuals with normal weight [ 135 ], other research has found no significant effects of vitamin D on inflammatory biomarkers in patients with obesity [ 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ]. Furthermore, studies on the effect of vitamin D supplementation on CRP serum levels in patients with obesity have yielded conflicting results [ 137 , 138 , 139 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ].…”
Section: Resultsmentioning
confidence: 99%